PERANCANGAN VIDEO ANIMASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN DORATOON DI SEKOLAH DASAR - Fajra Sinindya; Supratman Zakir; Jasmienti Jasmienti; Liza Efriyanti (LPPM Unbaja, 2024)
This research focuses on the problems found conclude that the problem obtained is that in delivering learning material, educators tend to use manual calculation methods and manual explanation techniques and only focus on printed books. Apart from that, the contents of printed books owned by students and teachers have different contents. The author created an animated mathematics learning video using Doratoon by considering these problems. It is hoped that the video can be used validly, practically and effectively in elementary school mathematics lessons. Research and Development (R&D) methods were applied in this research. In this research, a 4D development model is applied which consists of defining, designing, developing and disseminating. The link address used by teachers and students is the result of research from animated learning videos. The author's product testing results show that the product passed the validity test from 4 experts with a score of 0.88 in the very valid category, the practicality test from 6 practitioners with a score of 0.96 in the very high category, and the effectiveness test from 27 students with a score of 0.94 in the high effectiveness category.